MODERN ASPECTS OF PATHOGENESIS OF UTERINE FIBROIDS - Khazratkulova, Kh.U.; Sadikova, D.R. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
This literature review devoted to modern aspects of pathogenesis of uterine fibroids, which are the most common gynecological diseases in women. Some exogenous factors: as traumatic, infectious, endogenus factors: hormonal, endocrine, genetic, inflammatory diseases are main significance to develop uterine fibroids, exactly, there is a clear relationship between vitamin D deficiency and increase the risk of developing uterine fibroids.